EO9: relationship between DT-diaphorase levels and response in vitro and in vivo. - Collard, J. (1995)
EO9 [3-hydroxy-5-aziridinyl-1-methyl-2(1H-indole-4,7-dione)-prop-beta-en- alpha-ol] was selected for clinical trial in Europe because of its preclinical profile but also because of its distinct mechanism of bioactivation. Several studies have shown that cells rich in DT-diaphorase may be particularly sensitive to EO9. The present study examined the relationship between DT-diaphorase activity and sensitivity to EO9 in a panel of cell lines largely derived from human and rodent leukaemias/lymphoma and solid tumours. A possible relationship between chemosensitivity and enzyme activity was demonstrated (correlation coefficient 0.796). A number of the human cell lines were established as xenografts in nude mice but, with the exception of HT29, DT-diaphorase specific activity was greatly reduced compared with the corresponding cell lines. These data suggest that in vitro studies of bioactivation of drugs by specific enzymes is unlikely to be relevant for the same tumour in vivo. Except for HCLO, all xenografts failed to respond to EO9 as a single dose. HT29 tumours in vivo had similar DT-diaphorase activity [359 nmol of 2,6-dichlorophenol-indophenol (DCPIP) reduced per min per mg of protein] to the cell line (337) but failed to respond to a single dose or daily dose schedule. A preliminary attempt to investigate an hourly dose schedule demonstrated a modest anti-tumour effect accompanied by enhanced toxicity. Attempts to optimise EO9 exposure parameters to potentiate activity in tumours with high DT-diaphorase activity are under way, but as yet the relevance of this particular enzyme for in vivo EO9 activity requires further investigation.